2020
DOI: 10.1016/j.molstruc.2020.128918
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure, chemical reactivity, kinetic and thermodynamic studies of new ligand derived from 4-hydroxycoumarin: Interaction with SARS-CoV-2

Abstract: Highlights New coumarin derivative (4-[( pyridin -3- ylmethyl ) amino ]−2 H -chromen-2-one) (L TA ) was synthesized and characterized by spectroscopic techniques. The ligand was characterized by single-crystal X-ray diffraction method and optimized by DFT method. The chemical reactivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Even though few studies ( Ait-Ramdane-Terbouche et al, 2020 , Chidambaram et al, 2020 , Koparir, 2020 , Kumar et al, 2020 , Lyndem et al, 2020 , Maurya and Mishra, 2021 , Milenković et al, 2020 , Mishra et al, 2020 ; M Özdemir et al, 2020; Mücahit Özdemir et al, 2020; Yañez et al, 2020 ) have been reported on coumarin analogues interactions against SARS-CoV2, and reported that the compounds are showing good binding affinity, there are other coumarin derivatives that are not studied and there is no much multitargeted studies on coumarines which can help to find a single compound to interact with the multiple targets which are responsible for the entry into human, replication and virulence of SARS-CoV2. Moreover, the coumarin derivatives are reported for having good anti-inflammatory activity which can help to improve the inflammation caused by SARS-CoV2.…”
Section: Introductionmentioning
confidence: 99%
“…Even though few studies ( Ait-Ramdane-Terbouche et al, 2020 , Chidambaram et al, 2020 , Koparir, 2020 , Kumar et al, 2020 , Lyndem et al, 2020 , Maurya and Mishra, 2021 , Milenković et al, 2020 , Mishra et al, 2020 ; M Özdemir et al, 2020; Mücahit Özdemir et al, 2020; Yañez et al, 2020 ) have been reported on coumarin analogues interactions against SARS-CoV2, and reported that the compounds are showing good binding affinity, there are other coumarin derivatives that are not studied and there is no much multitargeted studies on coumarines which can help to find a single compound to interact with the multiple targets which are responsible for the entry into human, replication and virulence of SARS-CoV2. Moreover, the coumarin derivatives are reported for having good anti-inflammatory activity which can help to improve the inflammation caused by SARS-CoV2.…”
Section: Introductionmentioning
confidence: 99%